Analisis Kepuasan Pelanggan Mie Gacoan - Bella Bunga Sejagad; Mutiara Anisa Titian Trisna; Syamsul Hidayat (BADAN PENERBIT STIEPARI PRESS, 2024)
In this era, various culinary businesses with uniqueness and excellence are emerging rapidly. With the development of this culinary business, the number of restaurants both regular restaurants and fast food restaurants is increasing. When consumers choose a restaurant as a place to eat, they not only see the quality of the food, but also the quality of the service. Therefore, the management must provide good service and product quality in order to compete with other restaurants and attract more customers. Customer satisfaction is determined by a good and friendly service system and a clean and comfortable location. This study aims to determine and analyze the level of product quality and service quality on customer satisfaction of gacoan noodles. The type of research used is quantitative by distributing questionnaires to gacoan noodle customers. The analysis techniques used in this study are classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination test.